Potential causes of subfertility in patients with intramural fibroids. Issue 1 (December 2015) - Pier, Bruce; Bates, G.
Abstract Background Intramural leiomyomas have been long debated as a potential cause of infertility and pregnancy loss. Findings Previous research has linked intramural fibroids to defective implantation, as well as to abnormal peristaltic events of the uterine smooth muscle. Previous reports describe the effects of intramural fibroids on normal human fertility and early pregnancy loss, specifically in regards to implantation failure. Conclusion A thorough understanding of prior research may direct new research focus, leading to better understanding of leiomyoma-associated infertility.